Peripapillary hyperreflective ovoid mass-like structures: prevalence and associations in the adult population of the Beijing Eye Study - Jonas, Jost B.; Panda-Jonas, Songhomitra; Milea, Dan; Lamirel, Cédric; Xu, Jie; Jonas, Rahul A.; Wang, Ya Xing (Investigative ophthalmology & visual science, 2025)
To assess prevalence and associations of peripapillary hyperreflective ovoid mass-like structures (PHOMS) on optical coherence tomographic images in a general adult population. Participants in the population-based Beijing Eye Study underwent ocular and systemic examinations. Using optical coherence tomographic optic nerve head images, we assessed presence and location of PHOMS. The study included 963 eyes (age, 64.1 ± 9.5 years; axial length, 23.05 ± 1.02 mm). PHOMS detected in 15 eyes (1.6%; 95% confidence interval [CI], 0.0-2.1) extended over 30°, 60°, and 90° in 4 (27%), 6 (40%), and 5 (33%) eyes, respectively. The PHOMS were located at 2 o’clock (referring to right eyes) in two (13%), at 3:00 h (n = 1), 5:30 h (n = 1), 6:00 h (n = 2), 6:30 h (n = 1), 7:00 h (n = 2), 8:00 h (n = 1), 8:30 h (n = 2), 9:30 h (n = 2), and at 10:30 h (n = 1). On multivariable analysis, higher PHOMS prevalence was associated with smaller optic disc size (odds ratio [OR], 0.05; 95% CI, 0.01-0.28; P < 0.001), thicker peripapillary retinal nerve fiber layer (OR, 1.13; 95% CI, 1.04-1.22; P = 0.004), thicker retinal pigment epithelium-Bruch’s membrane complex thickness (OR, 1.70; 95% CI, 1.19-2.43; P = 0.04), and longer axial length (OR, 2.14; 95% CI, 1.12-4.08; P = 0.02). It was not associated with best-corrected visual acuity, perimetric indices, or any other ocular or systemic parameter or disease examined. PHOMS are relatively rare in the general adult and elderly population and mainly associated with a small optic disc. They are not related to a decrease in visual function or peripapillary retinal nerve fiber layer thickness, and they do not indicate an optic nerve damage. They are unrelated to other major ocular and systemic diseases, although they may be due to a localized crowding of peripapillary nerve fibers in eyes with small (crowded) optic discs.
Gesehen am 25.11.2025